Experimental study on the efficiency improvement of flat plate solar collector using hybrid nanofluids graphene/waste cotton - Mahamude, Abu Shadate Faisal; Wan Sharuzi, Wan Harun; Kumaran, Kadirgama; Devarajan, Ramasamy; Farhana, Kaniz; Salih, Khalid; Yusaf, Talal (MDPI AG, 2022)
Flat plate solar collector can easily be termed as the most vastly studied alternative energy transforming and generating technology of the twenty-first century. As the world is racing towards the fourth industrial revolution (Industry 4.0), more and more energy is being consumed for mega projects to be materialized. Electronic devices are not only confined to conventional intermittent costlier electric energy let alone on fuel. Solar energy is now being shared to operate smart devices, transformed electric energy, automobiles, aeronautics, water heating, and space heating. Traditional flat plate solar collector can only occupy 50-60% of their thermal efficiency resulting in less heat generation and low thermal performance because of using a common absorber made of copper tubing adjacent to a high conductive metal sheet (copper or aluminum). To ameliorate the thermal efficiency of the solar collector it is imperative to find out a superior alternative heat exchanger that will result in improved thermal performance of the solar collector. In this study, light has been shed in terms of substituting conventional heat absorbers by crystal nano-cellulose (CNC) and graphene hybrid.